1986
DOI: 10.1002/sia.740090402
|View full text |Cite
|
Sign up to set email alerts
|

Surface analysis and the complexity of real catalysts

Abstract: This paper is written for specialists of surface techniques not perfectly familiar with catalysis, as well as for scientists working in the area of heterogeneous catalysis. It is aimed at suggesting the problems of characterization that surface analysis is faced with, because of the complexity of real catalysts. We first present the various typical 'architectures' to which catalysts may correspond. We shall then illustrate typical prohlems, and their solutions, by selecting examples in the field of hydrodesulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The nature of the active species and the mechanism of catalytic action remain a subject of debate. For example, Delmon cataloged a dozen theories explaining the behavior of these catalysts , These investigators subsequently showed that these Co atoms on the edges of the MoS 2 layers seem to be located in the same plane as the Mo atoms, with a Mo−Co distance of 0.28 nm, which is close to that observed in Co−Mo−S cluster compounds.…”
Section: Introductionmentioning
confidence: 84%
“…The nature of the active species and the mechanism of catalytic action remain a subject of debate. For example, Delmon cataloged a dozen theories explaining the behavior of these catalysts , These investigators subsequently showed that these Co atoms on the edges of the MoS 2 layers seem to be located in the same plane as the Mo atoms, with a Mo−Co distance of 0.28 nm, which is close to that observed in Co−Mo−S cluster compounds.…”
Section: Introductionmentioning
confidence: 84%
“…For example, Delmon cataloged a dozen theories explaining behavior of these catalysts. 5 Topsge and his colleagues established that the basic structural units are small MoS2-like domains with Co atoms on the edges of the layers in the structure.6.7 These investigators subsequently showed that these Co atoms on the edges of the MoS2 layers seem to be located in the same plane as the Mo atoms, with a Mo-Co distance of 0.28 nm, which is close to that observed in Co-Mo-S cluster compounds.8…”
Section: Introductionmentioning
confidence: 86%
“…Important properties such as activity, selectivity and also poisoning of a catalyst are determined by the chemical species on its surface [1][2][3][4][5][6]. with characteristic results.…”
Section: Introductionmentioning
confidence: 99%